Labour Policy and Diplomacy: Argentina’s Labour Attachés under Peronism - Damilakou, Maria (Historein, 2020)
This article analyses Argentina’s labour attaché programme established under Perón’s governments from 1946 to 1955. Contrary to the US and British labour attaché programmes set up during wartime, Perón created a class-based diplomatic service, manned by rank-and-file trade union members. The institution of these “plebeian” diplomats, who made contact with the local labour movement and publicised Argentina’s corporatist model in the countries to which they were assigned, reflects Perón’s political programme, based on the privileged relationship of mutual support he built up with trade unions, as well as the deep social transformations that took place in Argentina during the Peronist era. Argentina’s labour attaché programme also reflects Perón’s regional and global aspirations in which an “alternative” labour internationalism, inspired by Peronist ideals and the Third Way position, and opposed to both capitalism and communism, played a key role. The article focuses on the concept, continuities and oscillations of Perón’s labour diplomacy from 1948 to 1955, as well as on the action plan and working methods of his labour attachés, while showing the serious constraints they faced due to the very nature of the Peronist regime and the dynamics of the dualistic Cold War context.